2020
DOI: 10.1111/adj.12776
|View full text |Cite
|
Sign up to set email alerts
|

Web‐based information on orthodontic clear aligners: a qualitative and readability assessment

Abstract: Background Data regarding the quality of information (QOI) related to orthodontic clear aligners (OCAs) on the internet are lacking. The aim of the present investigation was to assess the quality and readability of websites providing information regarding OCAs to prospective patients. Methods Three search terms were entered separately into three search engines. Four validated QOI instruments were used to determine the QOI and readability of the content contained within the websites that satisfied predetermined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 32 publications
5
40
2
Order By: Relevance
“…For this reason, it may be more useful to evaluate the results with additional instruments. In our study, only four websites had the HONcode seal (4/111; 3.6%), which was more than in previous studies about adult orthodontics [30] and CAT [32], but much lower than in a recent study about periodontal diseases [24]. In addition, all websites with HONcode certification belonged to professional organizations.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…For this reason, it may be more useful to evaluate the results with additional instruments. In our study, only four websites had the HONcode seal (4/111; 3.6%), which was more than in previous studies about adult orthodontics [30] and CAT [32], but much lower than in a recent study about periodontal diseases [24]. In addition, all websites with HONcode certification belonged to professional organizations.…”
Section: Discussioncontrasting
confidence: 81%
“…This was comparable to not only the number of evaluated websites in previous studies but also the real online search behavior of a potential patient K [30,32]. Together with the exclusion criteria, our search strategy was very similar to previous studies [4,31,32]. The display of the HONcode seal on a medical website can be regarded as meaning it presents understandable, accessible, and reliable information.…”
Section: Discussionsupporting
confidence: 76%
“…39,40 It is similar to the mean overall DISCERN score of 33 related to the websites of four DTC orthodontic aligner providers in a study assessing the quality of information regarding clear orthodontic aligners provided by a variety of online authors. 24 It is, however, less than the DISCERN scores of 36.3-65.7 found in studies which have investigated the quality of online information related to orthodontic treatment modalities, adult orthodontics, lingual orthodontics, orthodontic temporary Quality of DTC aligner provider websites anchorage devices, ankyloglossia and obstructive sleep apnoea. 4,5,7,39,41,42 The variation in mean scores for individual DISCERN items indicated that some aspects of content reliability and the quality of information regarding treatment choices were better addressed than others.…”
Section: Discussionmentioning
confidence: 99%
“…27 The search strategy involved the three most commonly used search engines worldwide and search terms used in a similar study. 24 The intention of the strategy was to identify and evaluate as many DTC aligner providers as possible. The high number of replicated websites indicated that search engine preference made little difference to the results of the search terms used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation